Hydrogen sulfide protects retina from blue light-induced photodamage and degeneration via inhibiting ROS-mediated ER stress-CHOP apoptosis signal - Sen Zhu; Xuan Li; Bingrong Dang; Fen Wu; Kexin Gou; Chunming Wang; Changjun Lin (Taylor & Francis Group, 2022)
Background: Hydrogen sulfide (H2S) is a small reducing gas molecule with various biological functions such as anti-oxidative, anti-apoptotic and anti-inflammatory activities. In this study, we investigated the therapeutic effects of exogenous H2S in the experimental models of retinal photodamage in vivo and in vitro.Methods: Rats with open eyelids were pretreated with H2S (80~120 μmol/kg) for 10 days and then continuously exposed to blue light (435~445nm, 11.2W/m2) for 8 h to establish in vivo experimental model. ARPE-19 cells were pretreated with H2S and then exposed to blue light to establish in vitro experimental model.Results: In vivo experiments, H2S significantly ameliorated blue light-induced retinal oxidative stress, apoptosis and degeneration. Moreover, H2S inhibited the activation of blue light-induced endoplasmic reticulum (ER) stress CHOP apoptotic signaling. In vitro experiments, H2S improved blue light-induced oxidative stress and oxidative damage. H2S inhibited ROS-mediated activation of ER stress CHOP apoptotic signaling. H2S alleviated blue light-induced apoptosis and increases cell viability. The ER stress inhibitor 4-PBA alleviated blue light-induced apoptosis and increases cell viability.Conclusion: Taken together, these results indicate that H2S can inhibit ROS-mediated ER stress-CHOP apoptosis signal, thereby alleviating blue light-triggered retinal apoptosis and degeneration.